Miriame Dimulu: capstone - Dimulu, Miriame, artist (Colorado State University. Libraries, 2024)
The artist's statement: Throughout my entire time at CSU, I dedicated myself to enhancing my skills as a designer. With a concentration in graphic design, I have not only been able to experiment extensively with my design work but also to find my place in this industry as an artist. This period of exploration has allowed me to delve into other areas, including motion graphics, which I pursued throughout this semester. My journey has been me continuously challenging myself to push the boundaries of traditional design. As I move forward, I am eager to bring this dynamic blend of skills and passionto professional projects, aiming to create impactful, visually compelling designs as well functional designs for people.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design